The answer would be B 21/4
Answer:
x=-2, y=-6
Step-by-step explanation:
Simple substitution.
Since y is isolated in one of the equations already, you can plug it into the second equation.
x - 2(3x) = 10
x - 6x = 10
-5x = 10
x = -2
Sub. x = -2 into 3x = y:
3(-2) = y
y = -6
Step-by-step explanation:
3
hope it helps u.......
Answer:
(5.4582 ; 6.8618)
Step-by-step explanation:
Given the data:
6 10 2 6 3 3 3 6 6 6 6 5 8 9 10 10 7 9 3 6 5 10 9 9 10 3 8 6 6 3 3 6 6 5 4 10 9 3 5 7 10 6 3 8 6 8 3 3 5 5
Sample mean, xbar = Σx / n
n = sample size = 50
ΣX = 308
xbar = 308 / 50 = 6.16
Using a Calculator :
The sample standard deviation, s = 2.469
Confidence interval = xbar ± margin of error
Margin of Error = Tcritical * s/sqrt(n)
Tcritical at 95% ; df = 50 - 1 = 49
Tcritical = 2.010
Hence,
Margin of Error= 2.010 * (2.469/sqrt(50)) = 0.7018
Lower boundary : (6.16 - 0.7018) = 5.4582
Upper boundary : (6.16 + 0.7018) = 6.8618
(5.4582 ; 6.8618)
Answer:
x = -3 and y = -4
x + y = -3-4 = -7
Step-by-step explanation:
-4x + 9y = -11 ------------------------------------------------------------------------(1)
-3x + 7y = -9--------------------------------------------------------------------------(2)
multiply through equation (1) by 3 and multiply through equation(2) by 4
-12x + 27y = -33 -----------------------------------------------------------------------(3)
-12x + 28y = -36 ----------------------------------------------------------------------(4)
subtract equation (1) from equation (2)
y = -3
substitute y = -3 into equation (2)
-3x + 7(-3) = -9
-3x -21 = -9
add 21 to both-side of the equation
-3x -21 + 21 = -9 + 21
-3x = 12
divide both-side of the equation by -3
-3x/-3 = 12/-3
x = -4
x = -3 and y = -4